ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (Studi pada PT. Poliplas Indah Sejahtera) - Nariswari, Linggar; Rahardjo, Mudji (Diponegoro Journal of Management, 2016)
This research is motivated by the research gap and phenomena that exist in PT. Poliplas Indah Sejahtera. This study aims to analyze the effect of transformational leadership style and organizational culture on employee job satisfaction.This study uses a transformational leadership style and organizational culture as an independent variable, and employee job satisfaction as the dependent variable. Based on the formula Slovin, respondents drawn in this study were as many as 80 employees. Processing data using multiple linear regression.            Based on the results of instrument test, the indicators used in this study proved to be valid and reliable. Based on the classic assumption test, there is no symptoms of multicollinearity, heteroscedasticity does not happen, and the data can be distributed normally. Based on the multiple linear regression test, transformational leadership style and organizational culture has a positive and significant impact on employee job satisfaction at PT. Poliplas Indah Sejahtera, either partially or simultaneously. Linear regression equation of the relationship between the variables in this study are: Y = 0,436X1 + 0,196X2.